(untitled) (Revista de História da UEG (REVHIST), 2021)
The article it presents aims to bring an analysis of the tomb collection of Santana Cemetery in the city of Goiânia, based on the relationship between memory and identity. The temporal return for such an undertaking is delimited between the 1940s and 1950s, justified here, as it is a significant period of approximation between public and ecclesiastical power. One of the aims of this approach was an effective involvement by the Catholic Church in the figure of D. Emanuel Gomes de Oliveira, then archbishop of Goiás in establishing a predominant religious identity in the young capital. Thus, as sculptural representations present in the necropolis of Goiânia, they are observed here from context in which historical, political, aesthetics and cultural aspects. Keywords: Santana Cemetery. Memory. Identity. Religiosity. Tomb sculpture.